Occupational stigma perception and public employees' burnout: A moderated moderation model of work–family conflict and social comparison - Rubinia C. Bonfanti; Giulia Foti; Gabriele Giorgi; Stefano Ruggieri (Acta Psychologica)
Background: The prevalence of burnout symptoms has become very high among public employees, with occupational stigma perception as an important predictor of burnout. Combining personal and relational factors can effectively exacerbate burnout symptoms. The study explores how work–family conflict and social comparisons orientation (both upward and downward) influence the relationship between occupational stigma perceptions and burnout among Italian public employees, applying Conservation of Resources Theory. Methods: We measured burnout, occupational stigma perception, work–family conflict, and social comparison orientation using cross-sectional, anonymous, self-reported questionnaires filled out by 305 employees. Results: The correlation analysis revealed that burnout positively related to upward comparison, work–family conflict, and occupational stigma perception and negatively related to downward comparison. Linear regression analysis indicated that occupational stigma perception was significantly associated with increased burnout symptoms in public employees. The moderation analysis showed that work–family conflict positively moderated the positive relationship between occupational stigma perception and burnout (β = 0.061, p < .001). Moderated moderation analyses only support the role of upward social comparison as a moderator of the role of work–family conflict (β = 0.040, p < .01). Conclusion: The study theoretically enhances understanding of the links between occupational stigma, work–family conflict, social comparison orientation, and burnout, while highlighting the practically need for organizations to address psychosocial factors to reduce burnout. Organizations that recognize the influence of these factors on employee well-being can implement timely preventive and management strategies to address these challenges.